ODNOWA PARAFII – PASTORALNE WSKAZANIA JANA PAWŁA II - Biela, Bogdan (Studia Pastoralne, 2023)
The need for a decent vision of the parish rooted in the teaching of the Church which results from a deep theological reflection and is based on pastoral experience, opened on its suggestions to the contemporary context and able to reach out to the future is one of the most important needs of the contemporary Church. It is precisely the theological and pastoral vision created and propagated with dedication by John Paul II during almost twenty-eight years of his pontificating. The vision has a major motive – it is supposed to become a missionary community on the one hand, and from the practical point of view it should become a community of communities. The conditioning of the parish is mutual in this respect. If one wishes to put into practice this model of a parish, one has to bear in mind the four dimensions of pastoral activities: the trinitarian dimension – the mystery of God; the ecclesiological dimension – the mystery of the Church; the canonical dimension – the legal and structural reality; and the humanistic dimension. This theology of a parish should be the purpose of its renewal and should be treated as a perpetual process, a specific lifestyle and mode of acting and, as consequence, should also serve as an impulse for the development of practical implementations of parishes that function in a specific social and cultural context.